Enzymatic and hemolytic properties of Propionibacterium acnes and related bacteria. - Hoeffler, U (1977)
The production of chondroitin sulfatase, hyaluronidase, deoxyribonuclease, gelatinase, phosphatase, lecithinase, and hemolysins was examined in 95 strains of Propionibacterium acnes and four related species of anaerobic, respectively, microaerophilic coryneform bacteria (P. avidum, P. lymphophilum, P. granulosum, and Corynebacterium minutissimum). All enzymes could be demonstrated in at least one representative of the species tested. Those Propionibacterium species most frequently found in acne vulgaris lesions, i.e., P. acnes and P. granulosum, proved to be the most active organisms concerning the production of the enzymes tested. P. avidum, on the other hand, showed the highest rate of hemolytic activity.